Prospective Evaluation of Post-Operative Weight Changes among Children After (Adeno)-Tonsillectomy - Khaled Hassen; Agila Albarasi; Yousef Hasen; Amira Mohammed; Marfoua Ali (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. This study was aimed at demonstrating the relationship between tonsillectomy and weight change in children. Methods. This study was conducted in the Department of Otolaryngology at Al-Bayda Medical Center, Libya, between July 2019 to June 2020. A study analyzed the patients who underwent tonsillectomy with or without adenoidectomy, grommet insertion, or adenoidectomy alone by measuring their weight and height before and after the procedure six months postoperatively. Results. Weight was changed significantly (P=0.001) in children who underwent adenotonsillectomy surgery pre- and post-operatively (at 1, 3, and 6 months). Pre-operative weight was (21.83±10.85) and post-operative weight was (23.06±10.99), (23.75±11.20), and (24.79±11.55) at 1, 3, and 6 months, respectively. In comparison of pre- and post-operative body mass index (BMI). The change in pre-operative BMI was 15.82 2.98 and post-operative BMI was 17.68 ±3.08. The result of the comparison was statistically significant (p=0.001). BMI grade changed in pre- and post-operative settings as follows: underweight pre- (72.5%), post-operative (2.5%), average weight recorded in pre- (25%), post-operative (82.5%), overweight found in pre- (2.5%), post-operative (10%), and obese found in pre- (0%), post-operative (5%) with statistically significant (P=0.001). Conclusion. There was an increase in weight gain post-tonsillectomy with or without adenoidectomy. The difference was mostly observed six months post-operation, with a positive linear correlation between weight and BMI.